Clinical researchInflammatory process modulation in children with cystic fibrosis submitted to aerobic training - de Oliveira, Ana Carolina N.; de Oliveira, Julio Cesar M.; Mesquita-Ferrari, Raquel A.; Damasceno, Neiva; Oliveira, Luis V.F.; Sampaio, Luciana M.M. (Archives of Medical Science, 2009)
Introduction: Systemic inflammatory response in cystic fibrosis (CF) alters exercise capacity. The aim of the present study was to assess the systemic inflammatory process through C-reactive protein levels and the capacity for aerobic exercise in patients with cystic fibrosis submitted to physical training. Material and methods: A controlled, prospective clinical trial was carried out on a consecutive sample were twenty Caucasian children, with a mean age of 13.21 years. Two groups of patients with CF were formed: one group submitted to physical training (G1) and one group without physical training (G2). The experimental protocol was made up of medical history, lung function test, step test, cardiopulmonary exercise test and collection of blood samples. Results: Prior to the experiment, lung function and systemic C-reactive protein in the patients with CF underwent correlation analysis. A moderately significant = –0.62, pr relationship was found between FEV1 and CRP (< 0.01). Pre-training and post-training values were compared at the end of the six-week period. There was a significant increase in the number of steps in G1 alone, with a reduction in dyspnea, HR and leg fatigue. Conclusions: We may infer that aerobic exercise training maintained the inflammatory process stable and increased exercise capacity in patients with CF. Thus, the measurement of systemic inflammatory response may be a variable to determine whether a proposed training program will trigger greater inflammation.